The implementation of fiqh muamalah learning for children with intellectual disabilities at the state special school (slb) in magelang city - Anifa Rahmawati; Sigit Tri Utomo; Ana Sofiyatul Azizah; Abdul Hakim; Ahmad Mustafidin; Mas’udin (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2024)
The aim of this research is to determine the implementation of muamalah fiqh learning for mentally retarded children, supporting factors and inhibiting factors for muamalah fiqh learning for mentally retarded children in Magelang City State Special Schools. This research uses qualitative research methods, using a pedagogical approach. This type of research is research conducted in the field. The data sources used are primary data sources in the form of observations and interviews, as well as secondary data sources in the form of documentation results. Data collection techniques use observation, semi-structured interviews, and documentation. The data analysis technique in this research uses data reduction, data presentation, and drawing conclusions. Meanwhile, data triangulation uses data source triangulation, technical triangulation, and time triangulation. The results of the research show that muamalah fiqh learning for mentally retarded children at the Magelang City State Special School is integrated through PAI learning so that the learning is adapted to the needs and abilities of mentally retarded children. In learning Islamic jurisprudence, the material taught to mentally retarded children is the basics of buying and selling, such as the meaning of buying and selling, the law of buying and selling, and various types of buying and selling. There are two strategies used by PAI teachers in teaching mentally retarded children, namely individual strategies and behavioral strategies. Meanwhile, the methods used by PAI teachers in learning jurisprudence are lecture, question and answer, cooperative, and Contextual Teacing Learning (CTL) methods. The supporting factors for learning muamalah fiqh for mentally retarded children include adequate facilities and infrastructure, appropriate learning methods and strategies, and PAI teachers having a patient attitude in teaching mentally retarded children. Meanwhile, inhibiting factors include the lack of learning media used by teachers, the lack of PAI teachers in special schools, the absence of learning modules or books for students to use, and mentally retarded children who have different cognitive abilities from normal children.